Replies: 2 comments
-
Hi @dims12
shiftExpression
: unaryExpression
| shiftExpression ('*' | '/' | '%') shiftExpression
| shiftExpression ('+' | '-') shiftExpression
| shiftExpression ('<<' | '>>' | '>>>') shiftExpression
; Similarly, we can rewrite the expression
: lambdaExpression
| unaryExpression
| expression ('*' | '/' | '%') expression
| expression ('+' | '-') expression
| expression ('<<' | '>>' | '>>>') expression
| expression ('<' | '>' | '<=' | '>=' | 'instanceof') expression
| expression ('==' | '!=') expression
| expression '&' expression
| expression '^' expression
| expression '|' expression
| expression '&&' expression
| expression '||' expression
| <assoc=right> expression '?' expression ':' expression
| leftHandSide ('=' | '*=' | '/=' | '%=' | '+=' | '-=' | '<<=' | '>>=' | '>>>=' | '&=' | '^=' | '|=') expression
; |
Beta Was this translation helpful? Give feedback.
0 replies
-
I don't recommend using this grammar because it's slow and outdated. Use java instead. |
Beta Was this translation helpful? Give feedback.
0 replies
Sign up for free
to join this conversation on GitHub.
Already have an account?
Sign in to comment
-
Hi! I noticed that
additiveExpression
is never used here: https://github.com/antlr/grammars-v4/blob/master/java/java8/Java8Parser.g4#L1276`(Used only in itself and in
shiftExpression
)Is it by design of Java grammar is far from completeness?
Beta Was this translation helpful? Give feedback.
All reactions